2021
DOI: 10.3390/ijerph18147372
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment Syndrome during COVID-19: A Comparison of Three Population Groups

Abstract: Introduction: Of the serious problems that characterise the current crisis in Spain, the most alarming and revealing is unemployment, which, despite being so common, continues to be quite a negative experience for most people, often with serious negative effects on their biopsychosocial health. The perpetuation of this situation has given rise to a new syndrome of the unemployed. If these effects of economic downsizing are accompanied by the magnitude of the current situation brought about by COVID-19, the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…On the other hand, Pinilla et al (2021) showed that autonomous regions in Spain are most dependent on the service sector, especially tourism, as being the most negatively affected by Covit-19 shock and the associated confinement measures, revealing structural weaknesses in productive sectors in the Spanish economy. Bocchino et al (2021) argued that an unexpected and stressful factor such as COVID-19 may lead to feelings of vulnerability and helplessness, which affect personal health and lower productivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, Pinilla et al (2021) showed that autonomous regions in Spain are most dependent on the service sector, especially tourism, as being the most negatively affected by Covit-19 shock and the associated confinement measures, revealing structural weaknesses in productive sectors in the Spanish economy. Bocchino et al (2021) argued that an unexpected and stressful factor such as COVID-19 may lead to feelings of vulnerability and helplessness, which affect personal health and lower productivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, even though the labor market started to recover rapidly after the peak period of outbreak, the unemployment rate remained high, for example, in the United States, the unemployment rate remained at 6.9% in October 2020 (Yao and Wu, 2021). Bocchino et al (2021) concluded a new syndrome of the unemployed which is generally devastating for individuals and families. They found a greater symptomatology of the unemployment syndrome in the unemployed compared to the employed as stress, deterioration of the quality of life, low self-esteem, hopelessness, low personal satisfaction, anxiety, hostility, impotence, frustration, sleep pattern disorders, fear, feeling of irritability, and lack of adaptive resources and management of stressors.…”
Section: Unemployment Under Covid-19 and Associated Mental Health Pro...mentioning
confidence: 99%
“…They found a greater symptomatology of the unemployment syndrome in the unemployed compared to the employed as stress, deterioration of the quality of life, low self-esteem, hopelessness, low personal satisfaction, anxiety, hostility, impotence, frustration, sleep pattern disorders, fear, feeling of irritability, and lack of adaptive resources and management of stressors. Besides, the unemployed scored higher in abuse of alcohol, tobacco and other harmful substances, which may further develop into substance abuse without a proper coping strategy (Bocchino et al, 2021). Within all the named symptoms of the unemployed syndrome, losing the meaning of life and individual functioning is the most struggling for many individuals, which is the culprit that can give people the biggest blow (Thill et al, 2020;Levy and Cohen-Louck, 2021;Rosen and Stenbeck, 2021).…”
Section: Unemployment Under Covid-19 and Associated Mental Health Pro...mentioning
confidence: 99%
“…The research agenda includes examining how this unemployment crisis differs from previous unemployment crises, examining the nature of the grief evoked by the simultaneous loss of work and loss of life, acknowledging and addressing the privilege of scholars [16]. [6], [8] The purpose of this study is to provide insight into how COVID-19 has affected Indian unemployment. 120 million people may be forced back into poverty as a result of COVID-19induced economic disturbances, which might result in the loss of up to 135 million jobs.…”
Section: Introductionmentioning
confidence: 99%